Cytological diagnosis of undifferentiated carcinoma of the pancreas with osteoclast-like giant cells: report of three cases - Samanta, Swapan; Sharma, S. K. (Annals of Pathology and Laboratory Medicine, 2015)
Undifferentiated carcinoma of the pancreas with osteoclast-like giant cells is a very rare, highly malignant tumor of the exocrine pancreas and only few cases, diagnosed by Fine needle aspiration cytology (FNAC) have been reported till date. This tumor consists of two distinct cell populations composed of numerous multinucleated giant cells resembling osteoclasts of the bone and mononuclear stromal cells. Other heterogeneous cell populations may be present. We report three such cases in young patients with abdominal mass /digestive problems and rapid weight loss. Diagnoses were primarily made by FNAC and eventually confirmed by histopathology in tertiary centers.